Leaf area evolution and grain fulling period duration of three maize hybrids on two seeding dates - Endres, Valter Cauby; Mundstock, Claudio Mario (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at the UFRGS Agronomy Experimental Station In Guaíba, RS, Brazil, in order to compare the effects of temperature and radiation conditions occurring on two seeding dates on maize leaf area evolution. Three maize hybrids (Zea mays L.) (Pioneer 6872, Cargill 408, and Agroceres 28C) were sown on two seeding dates (Oct. 8, 1984, and Jan. 11, 1985). The number of days from emergence to silking and silking to physiological maturity were recorded as well as the grain-filling period. To the extent that seeding date was delayed, the vegetative period was reduced. From silking to maturity, solar radiation and air temperature were higher at the October sowing and the lower values at the second date contributed to a small reduction in the duration of the grain-filling period, independently of the hybrid. The integrated and per plant leaf area were smaller for the early hybrid and were not affected by the seeding date.